2008
DOI: 10.1007/s00415-008-0879-6
|View full text |Cite
|
Sign up to set email alerts
|

The OPTimization of Interferon for MS Study: 375 μg interferon beta-1b in suboptimal responders

Abstract: We aimed to evaluate the safety and MRI efficacy of interferon beta-1b (IFNbeta-1b) 375 microg (subcutaneously [sc] every other day [eod]) in relapsing-remitting multiple sclerosis (RRMS) patients with a suboptimal response to IFNbeta-1b 250 microg, i.e., with MRI activity or relapses. The OPTimization of Interferon for MS (OPTIMS) study was a prospective multicenter randomized phase 2 trial comprising a 6-month run-in phase (to identify suboptimal responders) and a 6-month randomized phase of open-label clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Exactly when to switch and which switch is most efficacious remains unclear, however. In the studies by Durelli et al 5 and Prosperini et al, 6 switching to a higher-dose IFN beta demonstrated improvement in MRI parameters but had less effect on relapse rates or disability measures. On the other hand, the studies by Caon et al 7 and Carra et al 9 did show some reduction in relapse rates when switching between IFN betas, albeit not as robust of an effect as when switching to another agent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Exactly when to switch and which switch is most efficacious remains unclear, however. In the studies by Durelli et al 5 and Prosperini et al, 6 switching to a higher-dose IFN beta demonstrated improvement in MRI parameters but had less effect on relapse rates or disability measures. On the other hand, the studies by Caon et al 7 and Carra et al 9 did show some reduction in relapse rates when switching between IFN betas, albeit not as robust of an effect as when switching to another agent.…”
Section: Discussionmentioning
confidence: 95%
“…Two studies have evaluated the effects of increasing the IFN beta dose in patients with suboptimal response. The first of these studies was performed by Durelli et al 5 In this prospective, randomized, phase II trial of 216 RRMS patients, 76 suboptimal responders to SC IFN beta-1b 250 µg QOD were analyzed. Suboptimal response was defined based on magnetic resonance imaging (MRI) criteria, the presence of a relapse, and/or confirmed disease progression.…”
Section: Evidencementioning
confidence: 99%
“…The latest news on this subject comes from the BEYOND study, 3 which did not show any superiority of 500 g IFN␤-1b every other day over 250 g IFN␤-1b. It remains a matter of speculation whether further dose optimizations can improve clinical efficacy, 9 and it is also unclear whether such short-term effects have any long-term consequences.…”
Section: Recent Head-to-head Trials: About Expectations Unsubstantiamentioning
confidence: 99%
“…Some indirect and direct evidence suggests that patients with suboptimal response to IFN may benefit from increasing the dose of IFN [42][43][44][45] . Other studies have shown that switching patients between first-line DMDs (IFN to GA and vice versa and from one IFN agent to another) reduced clinical disease activity in patients with suboptimally controlled MS, but these latter studies were small, observational, and uncontrolled 28,29,46 .…”
Section: Studies Of Switches Between First-line Agentsmentioning
confidence: 99%